2015
DOI: 10.1155/2015/919834
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role and Relationship between E2F1 and SV40 in Diffuse Large B-Cell Lymphoma of Egyptian Patients

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphomas worldwide. The pathogenesis of lymphomas is not yet well understood. SV40 induces malignant transformation by the large T-antigen (L-TAG) and promotes transformation by binding and inactivating p53 and pRb. L-TAG can bind pRb promoting the activation of the E2F1 transcription factor, thus inducing the expression of genes required for the entry to the S phase and leading to cell transformation. This immunohistochemical study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, E2F1 overexpression is known to contribute to the development and progression of OC, and this role is mediated by the p53-dependent apoptotic pathway and PI3K/AKT signaling pathway and microRNA activity (13, 31). More and more studies revealed that E2F1 overexpression could produce more aggressive tumors with a high proliferation rate and chemoresistance (3234). In our study, ONCOMINE and GEPIA datasets revealed that the expression of E2F1 was up-regulated in human OC, and E2F1 expression was linked with the clinical characteristics of patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…However, E2F1 overexpression is known to contribute to the development and progression of OC, and this role is mediated by the p53-dependent apoptotic pathway and PI3K/AKT signaling pathway and microRNA activity (13, 31). More and more studies revealed that E2F1 overexpression could produce more aggressive tumors with a high proliferation rate and chemoresistance (3234). In our study, ONCOMINE and GEPIA datasets revealed that the expression of E2F1 was up-regulated in human OC, and E2F1 expression was linked with the clinical characteristics of patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many molecular signatures have been shown to have prognostic value in DLBCL, such as TIM-3, PD-1, and E2F1 levels. [ 32 , 33 ] However, molecular markers are often costly and inefficient, making them unsuitable for clinical laboratories. By contrast, blood cell count is an inexpensive and easily available measure in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of molecular signatures have also shown prognostic roles, such as PD-1 and TIM-3 expression concentrations [25], E2F1 expression [26], nuclear and cytoplasmic NF-κB expression [27] and LincRNA-p21expression [28]. However, molecular marker is associated with high costs and time-consuming procedures and is not routinely available in most laboratories.…”
Section: Discussionmentioning
confidence: 99%